Triclosan coated sutures: an overview of safety and efficacy in reducing risk of surgical site infection - Sewlikar, Sandeep Arvind; Pillai, Reshmi Sujit; Mahajan, Nilesh Shailendra; Desai, Anish Ashok (International Surgery Journal, 2016)
Triclosan, a broad spectrum anti-microbial agent, is in the market for more than 40 years, mainly in personal care products. In 1972, triclosan has been introduced in health care industry, in surgical scrub. The use of triclosan effectively extended other products such as catheters, sutures and urethral stents. We have reviewed toxicity profile of triclosan and clinical publication on Triclosan Coated Suture (TCS). The available toxicity data establishes the acceptable profile of triclosan for using in human being. Till date, 5 systematic reviews and meta-analyses covering 20 randomized control clinical trials have been published, showing the efficacy of TCS in reduction of risk of surgical site infection. Additional, prospective studies are also available to support efficacy of TCS. This compilation may help surgeon to make a conscious decision to use TCS on the basis of evidences.